IMPROVED FUZZY-LOGIC ALGORITHM FOR CONTROL OF REACTIVE POWER AND VOLTAGE IN DISTRIBUTIVE NETWORKS - S. A. Perepelitsa; S. V Alekseeva; V. A. Sergunova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes a scheme for fuzzy-regulation of reactive power and voltage in electrical power network where static thyristor-controlled compensators are used as a source of reactive power. Description of formalized procedure pertaining to  fuzzy  regulator  in  the  form of  fuzzy  relations between controlled  (voltage) and controllable parameters of the network (current and reactive power of a condensator). An algorithm efficiency proposed for a fuzzy-logic regulator and used for regulation of static condensators has been shown on the basis of calculative experiments and an electric power network taken as an exemple